A STUDY ON THE EFFECTIVENESS OF USING ANIMATION MOVIE COMPARED TO CONVENTIONAL METHOD IN TEACHING NARRATIVE WRITING - Panjaitan, Nelson B.; Siringo-ringo, Esther Gladys; Hendriks, Anne Lou (Journal of Language Pedagogy, 2011)
Abstract: This study is entitled âThe Effectiveness of Using Animation Movie Compared to Conventional Method in Teaching Narrative Writing.â The purpose of this paper is to know whether or not there is a significant improvement in the studentsâ narrative writing after using the animation movie. The participants involved in this study were 60 pupils in tenth grade senior high school of SMAN 1 Parongpong, Bandung. Section C composed of 28 pupils, while the section D composed of 32 pupils. Section C was taught using conventional method while section D was taught using animation movie. This study involved four activities: pilot test, pretest, the implementation of experimental group and control group, and the posttest. The participants were asked to answer the questions given in the pretest and posttest. The data obtained were as follows: = 28, =32, Î± = 0.05, the mean of pretest of experimental group was 53.25 while the mean of pretest for control group was 54.57. After the treatment, the mean of posttest of experimental group was 61.37 and for control group was 56.42. From the findings, it was shown that animation movie was effective in improving studentsâ writing skills as compared to conventional method as indicated by statistical writing scores in posttest of experimental group.Â